Exploring enterprise architecture adoption in public sector organization: A case study of accountant general's department of malaysia - Othman M.M.; Ahmad N.A.; Bunjari H.; Ramli S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Digital government; Digital transformation; Enterprise Architecture; Malaysia; Public sector; Public sector organization